Creation Capacity and Dispersion Capacity the Role of Opportunity to Learn in Knowledge Creation Performance - Ratih Pratiwi; Dasmadi; Windi NR Wardhani; Yulekhah Ariyanti (ADI Publisher, 2020)
This article aimed to investigate the opportunity to learn into the capacity of creation (team orientation and learning) and the capacity of dissemination (memory and system orientation). The capacity of creation and dispersion can each increase practice and exploitation in the creation of knowledge. We use survey questionnaires to collect data from 145 members of IKAPI in Central Java. In this research, creation capacity and dispersion capacity are expected to increase knowledge creation performance. Providing opportunities for learning that is expected to be able to increase the creation capacity and dispersion capacity and potentially affect the increase in knowledge creation performance. This article provides information on the importance of providing opportunities to learn in developing and managing creation capacity and dispersion capacity that support the practice of exploration and exploitation and develop knowledge creation performance. In improving organizational competence it is important to provide learning opportunities as large as human resources so that they are able to provide accessibility to the exchange and creation of knowledge.